La silla-nodo compleja - Benazic Tomé, Renato (2011)
In this paper establishes the formal locally a field of complex dimension two, in the vicinity of an isolated singular point, whose Taylor series expansion (around the isolated singularity) has linear part with a zero eigenvalue. Such singularities are called chair-node complex.